Theory of urban fabrics: Planning the walking, transit/public transport and automobile/motor car cities for reduced car dependency - Newman, Peter; Kosonen, L.; Kenworthy, Jeffrey (Liverpool University Press, 2016)
The theory of urban fabrics is outlined showing how different types of cities are combinations of walking, transit/public transport and automobile/motor car fabrics based on their transport systems and the universal travel-time budget. The distances/transport speeds that generate these urban fabrics and their associated elements, functions and qualities are outlined, emphasising, for the first time, how tasks of statutory planning and transport planning are different in the three urban fabrics. The theory is demonstrated in the Finnish city of Kuopio and with data from the authors' Global Cities Database, concluding with three different statutory and strategic planning approaches.